Morpho-Physiological Screening of Some Selected Rice (Oryzae sativa) Varieties for Salinity Stress Tolerance in Gashua Yobe State Nigeria - Abubakar, Tijjani; Dunoma, Abdurrahman; Tahir, Tahir Sani (FUDMA Journal of Sciences, 2026)
Rice is one of the most important cereal crops and a primary food source for nearly half of the global population. In Nigeria, (Oryza sativa L.) is widely cultivated and consumed, but its production is increasingly threatened by environmental stresses such as salinity and drought, which significantly reduce yield and farmer productivity. This study evaluated the morpho-physiological responses of selected rice varieties to salinity stress at the Botanical Garden of the Department of Biological Sciences, Federal University Gashua, Yobe State, Nigeria. Eight rice varieties, comprising four improved types (Faro 42, Faro 44, Faro 61, And Nerica) and four local landraces (Yar Masaba, Yar Sani, Jamila, and Jarani Bazawara), were assessed using a pot experiment. Seedlings were transplanted into pots containing 4kg of soil and exposed to salinity treatments of 0, 3, 6, and 9 dS/m using sodium chloride (NaCl) one month after germination. The experiment followed a randomized complete design. Data were collected on germination percentage, plant height, leaf chlorophyll content, leaf area, 50% wilting, and regeneration potential, and analyzed using analysis of variance. Results showed that salinity significantly (P < 0.05) affected all measured parameters across the varieties. However, Faro 42, Faro 44, and Nerica demonstrated moderate tolerance by maintaining relatively higher growth and physiological performance. In contrast, Yar Sani was highly susceptible, showing marked reductions under increasing salinity. The findings highlight promising varieties for cultivation in salt-affected areas and emphasize the value of morpho-physiological traits in screening for salinity tolerance.